2017
DOI: 10.1080/09712119.2017.1371608
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rumen fermentation and methane production as affected by rambutan peel powder

Abstract: The current study was aimed to determine the effect of rambutan peel powder (RPP) supplementation on in vitro gas production, rumen fermentation characteristics and methane production. The experimental design was a completely randomized design and the dietary treatments were different levels of RPP supplementation at 0, 4, 8, 12, 16 and 20 mg/0.5 g DM. Under this investigation, RPP supplementation did not affect gas production kinetics and in vitro digestibility (p > .05). The concentration of NH 3 -N decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…The ratio of C 2 :C 3 was reduced as a result of the RP supplementation groups, which agreed with the data of Foi klang et al [22] who revealed that using grape pomace powder (GPP) supplement remarkably increased the total VFA and C 3 production, while rumen methane estimation was dra matically decreased in the supplemented treatments. Similarly, Gunun et al [23] also reported that C 3 was increased, while C 2 and C 4 were similar when supplementing with plants con taining of CT and SP less than 3% of total DMI. Norrapoke et al [24] who found that dietary of mangosteen peel powder (MSP) enhanced total VFA concentration, increasing C 3 , reducing C 2 :C 3 and methane production in the MSP sup plementation in swamp buffaloes.…”
Section: Ruminal Fermentation Blood Methane Estimation and Microbimentioning
confidence: 76%
“…The ratio of C 2 :C 3 was reduced as a result of the RP supplementation groups, which agreed with the data of Foi klang et al [22] who revealed that using grape pomace powder (GPP) supplement remarkably increased the total VFA and C 3 production, while rumen methane estimation was dra matically decreased in the supplemented treatments. Similarly, Gunun et al [23] also reported that C 3 was increased, while C 2 and C 4 were similar when supplementing with plants con taining of CT and SP less than 3% of total DMI. Norrapoke et al [24] who found that dietary of mangosteen peel powder (MSP) enhanced total VFA concentration, increasing C 3 , reducing C 2 :C 3 and methane production in the MSP sup plementation in swamp buffaloes.…”
Section: Ruminal Fermentation Blood Methane Estimation and Microbimentioning
confidence: 76%
“…The removal of protozoa by SP can decrease CH 4 production, as some populations of methanogens remain associated with protozoa as ectosymbionts and endosymbionts (Gunun et al., ; Patra & Saxena, ). In addition, CT suppress methanogenesis by reducing the methanogenic archaea either directly or by decreasing the protozoal populations, thereby decreasing methanogens symbiotically associated with the protozoal population (Cieslak, Szumacher‐Strabel, Stochmal, & Oleszek, ; Gunun et al., ). In this study, supplementation of MPM at 200 g/head/day increased propionate, while the acetate, C2:C3 and CH 4 production were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, when supplementation of CT at low to moderate concentrations could improve ruminal fermentation, nitrogen metabolism, while suppress methanogenesis; therefore, leading to the improvement of animal production (Anantasook, Wanapat, Cherdthong, & Gunun, 2015;Gunun et al, 2016;Patra & Saxena, 2010). SP are of interest as potential feed additives for ruminant because they reduce ruminal protozoal population, inhibit methane production and modulate ruminal fermentation patterns (Gunun et al, 2018;Holtshausen et al, 2009;Polyorach, Wanapat, Phesatcha, & Kang, 2015). Positive effects of plant containing CT and SP on daily gain and milk production have been demonstrated in the previous studies, as well as a protective effect on dietary protein in the rumen in order to promote duodenal absorption, minimize excretion of nitrogen and modify the acetate to propionate ratio in rumen fluid (Anantasook et al, 2015;Salem et al, 2011Salem et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that tannin based forages have anti-bloat and anthelmintic characteristics which improve the quality of meat and milk products, fatty acids composition and ruminant antioxidant status (Blackmon et al, 2016). In addition, these tannins containing plants also contribute to inhibit the enteric methane emission (Anantasook et al, 2016;Gunun et al, 2017). (Ngwa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%